P01.002 Evaluation of 31-P-MR-Spectroscopy in malignant glioma correlated with histopathological results and intraoperative fluorescence. (19th September 2018) - Freyschlag, C F; Kerschbaumer, J; Steiger, R; Pinggera, D; Gizewski, E R; Thomé, C
Abstract: Background: The diffuse infiltration of malignant gliomas underlines the necessity for utmost radicality in surgical treatment with respect to functional outcome. According to previous studies, fluorescence techniques and intraoperative imaging facilitate complete or supratotal resection. MR-algorithms may discover areas at high risk by perfusion, diffusion-weighted imaging and spectroscopy. Extensive preoperative investigation with 31-Phosphorus - MR - Spectroscopy (31PMRS) was hypothesized to determine energy-demand and cell-turnover in surrounding tissue in order to unveil information about infiltration into non-contrast enhancing tissue. Material and Methods: Patients who underwent surgery for malignant glioma in non-eloquent areas (n=16), were included in this prospective trial. All underwent preoperative standard MRI, with additional whole brain 31PMRS. In all patients, one voxel within the contrast-enhancing tumor (CE+), one voxel at the border (including CE+ areas and surrounding T2-hyperintensive (T2+)) and one distant voxel, purely including T2+ areas (amenable for supratotal resection) were determined by a neuroradiologist. After standardized application of 5-ALA, image guided craniotomy and frameless stereotactic biopsy were performed, followed by microsurgical resection. The metabolites correlated to the contralateral control, histopathology and fluorescence behavior. Results: Biopsies showed tumor cells and fluorescence in all but one tumor (93%), whereas tumor cells were encountered within the infiltration zone in 81% of biopsies with one positive sample without fluorescence. The surrounding tissue included tumor cells in 7 patients, 4 of which were fluorescence negative. Values for resynthesis (CE+/border/T2+: 1, 050 ± 0, 300/1, 029 ± 0, 290/1, 104 ± 0, 277), hydrolysis (0, 295 ± 0, 241/0, 294 ± 0, 259/0, 332 ± 0, 298), energy demand (5, 207 ± 13, 569/3, 938 ± 3, 383/3, 716 ± 2, 004) and membrane turnover (1, 367 ± 1, 277/1, 267 ± 1, 092/1, 122 ± 0, 649) were obtained. Membrane-turnover was significantly higher in CE+, border zone and also in the T2+ areas, when compared to the control (p>0, 001; p>0, 002). Conclusion: 31PMRS in malignant gliomas provided information on metabolic changes tumor and surrounding edema. There was a evidence of infiltration by tumor cells in biopsies regardless of intraoperative fluorescence.